Pharmacokinetics and Safety of Momelotinib in Subjects With Hepatic or Renal Impairment. (28th December 2017) - Xin, Yan; Kawashima, Jun; Weng, Winnie; Kwan, Ellen; Tarnowski, Thomas; Silverman, Jeffrey A.
Abstract: Momelotinib is a Janus kinase 1/2 inhibitor in clinical development for the treatment of myelofibrosis. Two phase 1 open‐label, parallel‐group, adaptive studies were conducted to evaluate the pharmacokinetics of a single 200‐mg oral dose of momelotinib in subjects with hepatic or renal impairment compared with healthy matched control subjects with normal hepatic or renal function. Plasma pharmacokinetics of momelotinib and its major active metabolite, M21, were evaluated, and geometric least‐squares mean ratios (GMRs) and associated 90% confidence intervals (CIs) for impaired versus each control group were calculated for plasma exposures (area under concentration–time curve from time 0 to ∞ [AUC∞ ] and maximum concentration) of momelotinib and M21. There was no clinically significant difference in plasma exposures of momelotinib and M21 between subjects with moderate or severe renal impairment or moderate hepatic impairment and healthy control subjects. Compared with healthy control subjects, momelotinib AUC∞ was increased (GMR, 197%; 90%CI, 129%–301%), and M21 AUC∞ was decreased (GMR, 52%; 90%CI, 34%–79%) in subjects with severe hepatic impairment. The safety profile following a single dose of momelotinib was similar between subjects with hepatic or renal dysfunction and healthy control subjects. These pharmacokinetic and safety results indicate that dose adjustment is not necessary for momelotinib in patients with renal impairment or mild to moderate hepatic impairment. In patients with severe hepatic impairment, however, the dose of momelotinib should be reduced.